Gendered Affective Economies of Male Sexual Violence Against Men in South Africa - Chitiki, Elizabeth (University of the Witwatersrand, Johannesburg, 2023)
Within the South African context, sexual violence against men is an under-researched phenomenon, and abuse against men is largely characterized by silence. This study focused attention on discursive and affective dimensions of societal responses to sexual violence against men (heterosexual, gay, bisexual, and transgender men). At the pinna core of this research was the interrogation of how male victim-survivors of sexual violence are constructed within contexts that are embedded with gender, sexuality, and masculinity governing ideologies. Concerning sexual violence against men, dominant sexual constructions of men perceive men as sexually promiscuous and always ready for sex. Then, one ought to pose a question about how men's sexual agency and subjectivity are constructed when one or more of these social constructs are violated in the case of sexual violence. Using data from online radio talk podcasts and virtual ethnographies, I analyse societal responses to male sexual violence. Data were analysed using Foucauldian Discourse Analysis in tandem with Affect theory. The results of this research are presented in three chapters. The first chapter of the analysis discusses victim worthiness and empathy in social constructions of male sexual violence. The second chapter of the analysis shows the humanization of a (de)humanized subject in understanding prison rape via affective tropes. The third chapter of the analysis discusses the unmasking of institutional culpability through affective economies of shared pain and rage. Thus, the findings of the study highlighted that particular discursive constructions and affective tropes are useful in the negotiation, and surfacing of particular subjectivities in connection to male sexual violence.
A thesis submitted for the degree of Doctor of Philosophy in the field of Psychology, in the Faculty of Humanities, School of Human and Community Development, at the University of the Witwatersrand, Johannesburg, in 2023.
Keywords: Male sexual violence; Rape; Victim-survivor; Masculinity; Affect; UCTD; SDG-5: Gender equality